Predictors of Turnover Intention among Nurses in Private Hospitals: A Cross-Sectional Study Using Logistic Regression Analysis - Risna Zubaidah; Mochammad Malik Ibrahim (Universitas STRADA Indonesia, 2026)
Background: Turnover intention among nurses remains a critical workforce challenge, particularly in private hospitals where staffing instability directly affects service quality, patient safety, and organizational costs. Despite extensive research, evidence integrating multiple psychosocial work factors within a single multivariate model in the Indonesian private hospital context remains limited. This study addresses this gap by simultaneously examining key determinants of turnover intention and identifying the most influential predictors. Purpose: This study aimed to identify independent predictors associated with turnover intention among nurses in a private hospital setting. Methods: A cross-sectional study was conducted among nurses at a private hospital in Indonesia in 2025. A total of 70 respondents were selected using purposive sampling from a population of 81 nurses. Data were collected using a validated and reliable structured questionnaire. Turnover intention was dichotomized into high and low categories for logistic regression analysis. Data were analyzed using descriptive statistics, bivariate analysis (chi-square), and multivariate logistic regression. Although the sample size was relatively small, the number of predictors included in the final model was limited to ensure model stability. Results: Bivariate analysis showed that work motivation, work stress, burnout, work–life balance, job demands, and job satisfaction were significantly associated with turnover intention (p < 0.05). Multivariate logistic regression identified high work stress (POR = 31.62; 95% CI: 3.65–273.55; p = 0.002), high burnout (POR = 12.35; 95% CI: 1.78–85.58; p = 0.011), and low work motivation (POR = 9.02; 95% CI: 1.24–65.60; p = 0.030) as independent predictors of turnover intention. Conclusion: Turnover intention among nurses is primarily driven by high work stress, burnout, and low work motivation. These findings highlight the need for targeted organizational interventions focusing on stress management, burnout prevention, and motivation enhancement to improve nurse retention in private hospitals.